Receptor-Drug Interaction: Europium Employment for Studying the Biochemical Pathway of G-Protein-Coupled Receptor Activation. (25th February 2008) - Antonio, Colabufo Nicola; Grazia, Perrone Maria; Marialessandra, Contino; Francesco, Berardi; Roberto, Perrone
Abstract : In medicinal chemistry field, the biochemical pathways, involved in 7-transmembrane domains G-protein coupled receptors (GPCRs) activation, are commonly studied to establish the activity of ligands towards GPCRs. The most studied steps are the measurement of activated GTP-α subunit and stimulated intracellular cAMP. At the present, many researchers defined agonist or antagonist activity of potential GPCRs drugs employing [ 35 S]GTPγ S or [ 3 H]cAMP as probes. Recently, the corresponding lanthanide labels Eu-GTP and Eu-cAMP as alternative to radiochemicals have been developed because they are highly sensitive, easy to automate, easily synthesized, they display a much longer shelf-life and they can be used in multilabel experiments. In the present review, the receptor-drug interaction by europium employment for studying the biochemical pathway of GPCR activation has been focused. Moreover, comparative studies between lanthanide label probes and the corresponding radiolabeled compounds have been carried out.